Desain Dan Realisasi Aplikasi Pengelolaan Nilai Siswa Berbasis Web Menggunakan Framework Codeigniter - herdiyatmoko, hendrik fery (Jurnal Informatika UPGRIS, 2022)
Student Assessment System is a student score processing system based on the K13 curriculum. The 2013 curriculum has four aspects of assessment, namely aspects of knowledge, aspects of skills, aspects of attitudes, and behavior. In the 2013 curriculum, especially in learning materials, there are materials that are streamlined and materials that are added. The streamlined material appears to be in Indonesian, Social Studies, PPKn, and so on while the added material is Mathematics. In this study, the authors found several problems that occurred at SMA Xaverius 1 Palembang, including the difficulty of distributing grades starting from the teacher then the homeroom teacher and finally the vice principal in the academic field according to the K13 curriculum. The second is how the student assessment system is carried out in an integrated manner by a system, so that the value data is centered on one data source. The third problem is how to give a deadline when entering grades, so that teachers and homeroom teachers are administratively orderly in entering student grades. The student grade management application is built with the Codeigniter 3 framework, which makes grade data centralized, and grade distribution fast. With the facility of limiting the time for input values, the teacher is in an orderly administration. Parents can monitor their child's study progress with access to the application to view student report cards..